Chapter Le costituzioni nel vissuto. Rimuovere gli ostacoli: dalla Resistenza alla Costituzione - Creati, Eva (Public History of Education. Teorie, esperienze, strumenti, 2022)
This paper aims at describing the experience carried on by some pupils attending the third years at the vocational institute "Sismondi-Pacinotti" in Pescia, in the scholastic year 2018-19. Thruogh lessons and theatral workshops, students have discussed the first article of the Italian Constitution.